Understanding Language Teaching: An Educational Perspective - Bhushan, Ravi (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Notwithstanding the prolonged debate on teaching methods, the concept of language teaching as such has remained less developed. It is not only gradually emancipating itself from the method debate through conceptual schemes, empirical studies and classroom observation, a more deliberate interpretation of second language teaching in terms of educational theory is needed. An educational interpretation of language teaching is clearly interdisciplinary; linguistics, sociolinguistics, cultural studies and educational theory. The model developed by two educational researchers Dunkin and Biddle (1974) for the study of classroom teaching distinguishes four main categories of variables; presage, context, process and product. In their seminal book The Study of Teaching, Dunkin and Biddle critically examine classroom teaching in terms of these essential factors/ relationships. Moreover this model identifies two principal actors; the language teacher and the language learner. The teacher like the learner brings to language teaching certain characteristics which have bearing on educational treatment; age, sex, previous education and personal qualities and social context. This paper would examine the educational dimension of second language teaching with an aim to equip a language teacher with effective tools of ELT.